Research on active power steady‐state security region considering TCSC. Issue 13 (14th December 2017) - Chen, Baoping; Lin, Tao; Chen, Rusi; Li, Yong; Xu, Xialing
Abstract : With the large‐scale access of renewable energy sources represented by photovoltaic power and wind power, and the extensive use of FACTS, power system is characterised by the fluctuation of power outputs and the variation of network parameters, resulting in the great change of the operation state of power system. Therefore, it is urgent to obtain active power steady‐state security region (APSSR) of power system, so as to carry on state awareness of static stability to provide guidance for preventive control and generation schedule. However, when using the conventional method to study APSSR of power system with variable network parameters caused by FACTS, such as thyristor controlled series compensator (TCSC), it is necessary to determine the inversion of the n ‐order matrix with variable parameter, resulting in the great increase in the calculation time. In order to overcome the above issue, a novel method based on equivalent power injection method (EPIM) is proposed. In detail, firstly, by adopting EPIM to deal with TCSC branch in network, the power through the TCSC branch is equivalent to the power injection of two nodes of the TCSC branch associated with the equivalent reactance of TCSC, resulting that TCSC affects APSSR by affecting power injections instead of network parameter. Secondly, the explicit expression of APSSR associated with the equivalent reactance of TCSC is derived theoretically, and two factors affecting APSSR, i.e. the equivalent reactance and the location of TCSC, are investigated, respectively. Further, it can be found that when using the proposed method to construct APSSR considering TCSC, it is not necessary to carry out the inversion of the matrix with variable parameter, which will greatly raise the calculation speed. Finally, the IEEE standard systems are selected as benchmarks to demonstrate the validity and superiority of the proposed method for the purpose of online estimation of APSSR of power system.